Beban Keluarga Penderita Skizofrenia yang Periksa di Poliklinik Jiwa Rumah Sakit Jiwa Propinsi Jambi - Rusmimpong Rusmimpong; Daryanto Daryanto; Netha Damayantie (STIKes Patria Husada Blitar, 2016)
Family has a role in the caring of schizophrenia patient at home. Schizophrenia patient have a clinical condition which can be the factors to be hospitalized or at home. The family ability was also a burden for the patients care. The purpose of this study was to know of the correlation of the clinical conditions of schizophrenic’s patient and the family burden who has family members with schizophrenia at Psychiatric Polyclinic of Asylum of Jambi Province. The design used cross sectional. The sample size was 95 families who have family members with schizophrenia and selected by purposive sampling. The variables were characteristic of schizophrenia patient, patient clinical condition, and the family burden. The collected data of family burden used Zarit Burden Interview (ZBI). The data were collected on July 23 until August 12, 2015. The data analyses used correlation. Family burden correlated with frequent of inpatient psychiatric hospital (r = 0.30) and positive and negative symptoms of schizophrenia patients (r = 0.26), but not correlated with the sick duration of schizophrenia patient (p = 0.475). Thus, nurses were expected to provide health education which was aimed to improve the knowledge and ability of the family to care the patients at home.